Proteomic investigation of human skeletal muscle before and after 70 days of head down bed rest with or without exercise and testosterone countermeasures - Dillon, E. Lichar (PLoS One, 2019)
INTRODUCTION: Long-term head-down bed rest (HDBR) results in musculoskeletal losses similar to those observed during long-term space flight. Agents such as testosterone, in addition to regular exercise, are effective countermeasures for reducing loss of skeletal muscle mass and function. OBJECTIVE: We investigated the skeletal muscle proteome of healthy men in response to long term HDBR alone (CON) and to HDBR with exercise (PEX) or exercise plus testosterone (TEX) countermeasures. METHOD: Biopsies were performed on the vastus lateralis before (pre) HDBR and on HDBR days 32 (mid) and 64 (post). Extracted proteins from these skeletal muscle biopsies were subjected to 2-dimensional gel electrophoresis (2DE), stained for phosphoproteins (Pro-Q Diamond dye) and total proteins (Sypro Ruby dye). Proteins showing significant fold differences (t-test p ≤ 0.05) in abundance or phosphorylation state at mid or post were identified by mass spectroscopy (MS). RESULTS: From a total of 932 protein spots, 130 spots were identified as potentially altered in terms of total protein or phosphoprotein levels due to HDBR and/or countermeasures, and 59 unique molecules emerged from MS analysis. Top canonical pathways identified through IPA included calcium signaling, actin cytoskeleton signaling, integrin linked kinase (ILK) signaling, and epithelial adherens junction signaling. Data from the pre-HDBR proteome supported the potential for predicting physiological post-HDBR responses such as the individual’s potential for loss vs. maintenance of muscle mass and strength. CONCLUSIONS: HDBR resulted in alterations to skeletal muscle abundances and phosphorylation of several structural and metabolic proteins. Inclusion of exercise alone or in combination with testosterone treatment modulated the proteomic responses towards cellular reorganization and hypertrophy, respectively. Finally, the baseline proteome may aid in the development of personalized countermeasures to mitigate health risks in astronauts as related to loss of muscle mass and function.